Abdominal Compartment Syndrome due to OHSS - Firoozeh Veisi; Maryam Zangeneh; Shohreh Malekkhosravi; Negin Rezavand (Tehran University of Medical Sciences, 2012)
Abdominal compartment syndrome is a dangerous clinical situation, usually following abdominal injuries &operations. It is seldom observed in patients with gynecologic and obstetric problems. Abdominal compartment syndrome may be consequence ovarian hyperstimulation syndrome. A 28-year-old woman presented as a sever ovarian hyperstimulation.The increased IAP indicated that OHSS may be considered a compartment syndrome. Abdominal compartment syndrome needs laparotomy or paracentesis for reduction of pressure.